Studi Morfometrik dan Status Konservasi Tuntong Laut (Batagur borneoensis) di Pusat Konservasi Tuntong Laut Suaka Margasatwa Karang Gading dan Langkat Timur Laut - Afifah Wasalna; Lazuardi (CV.ITTC INDONESIA, 2024)
The Painted terrapin (Batagur borneoensis) Conservation Center at the Karang Gading and East Langkat Wildlife Reserve serves as an ex-situ breeding site for the Painted terrapin (Batagur borneoensis). This study aims to obtain morphometric data from the morphology of the Painted terrapin (Batagur borneoensis)and to identify the parameters that contribute the most to the body weight of Painted terrapin (Batagur borneoensis) living in the Painted terrapin (Batagur borneoensis) breeding pond at SMKGLTL, Selotong Village, Secanggang District, Langkat Regency. This study uses a saturated sampling method. The measured morphometric traits include the length and width of the carapace, the length and width of the plastron, the neck length, the length and width of the head, the length and width of the front legs, the length and width of the hind legs, the length and width of the front and rear footpads, as well as the length of the tail and weight. The results indicate significant differences in body weight between different age periods. The average weight of the painted terrapin at the age of 2 years is 445g ± 112.8 (x̅±SD), while at the age of 3 years it increases to 777.5g ± 557.0 (x̅±SD). Statistical analysis shows that the parameters contributing most to the body weight of the painted terrapin (Batagur borneoensis) are carapace length (X1) with a coefficient of determination of 128.022, hind limb width (X11) with a coefficient of determination of 92.906, and hind limb length (X10) with a coefficient of determination of 58.599.